She - Dengri, Chetna (Research and Humanities in Medical Education, 2016)
The narrative dates back to a few weeks ago when I met a thirteen year old girl with a dazzling smile and brilliant eyes - only to discover that behind those eyes was a dark tale - three sisters, a dying mother, and an indifferent father.